Technology and Education Transformation in Africa: Challenges and Remedies - Oko, Ode Agi (Strukturasi: Jurnal Ilmiah Magister Administrasi Publik, 2025)
Technology is a pivotal tool in revolutionizing Education in the global sphere, and the African continent is no exception. The primary objective of this paper is to examine the role of Technology in reshaping Education in the 21st century, focusing on the core values, pros, and cons of Africa. Reflecting on the recent past, it has become clear that Technology has emerged as a powerful tool in reshaping Education across Africa, in tandem with the global penetration of Technology. The paper aims to examine the role of Technology in delivering Education in Africa, its importance, challenges, setbacks, and expected remedial measures to address these challenges. The paper will also examine the importance of Technology in the African region. Education is the bedrock and foundation of living and the nucleus of civilization worldwide. The advent of Technology has transformed the traditional classroom into a dynamic learning environment. Gone are the days when teaching was confined to textbooks and a blackboard. Today, digital tools and online resources have taken centre stage, making learning more engaging and stimulating. The study data were collected through the documentation of secondary sources, including a review of related historical archival records, journals, write-ups, and library research based on existing findings. The study concludes by recommending that Technology should receive wide attention to continually transform Education. To improve teaching and learning, it is essential to utilize these innovations, among others.